Influence of transdermal sequential hormone therapy on the endometrial safety and bleeding pattern in postmenopausal women - Skrzypulec, Violetta; Rozmus-Warcholińska, Wioletta (Menopause Review/Przegląd Menopauzalny, 2007)
Aim of the study: Evaluation of the effect of sequential transdermal hormone therapy on the endometrial safety and bleeding pattern in postmenopausal women. Material and methods: In a six-month (6 treatment periods, 28 days each) randomized study, 75 healthy postmenopausal women aged 48-53 (51±3) years were assigned to receive 50 micrograms/day of continuous transdermal oestradiol with sequential transdermal norethisterone acetate (NETA) in daily doses of 170 micrograms in a single transdermal patch. Endometrial biopsies were taken pre-study and at the end of the treatment, if treatment had lasted at least 3 months. Safety was to be assessed in terms of the incidence of hyperplasia. Results: No case of hyperplasia was recorded in the treatment group. At the beginning of the study atrophy was seen in 64.9% of women, proliferatory endometrium in 15.9% and secretory endometrium in 18.6% of women. At the end of the study atrophic patttern was seen in 11.4% of women, proliferative endometrium in 50.6% and secretory endometrium in 29.5% of women receiving sequential transdermal HRT. The ultrasound assessment of the endometrium showed an increase in thickness (2.9±1.5 mm at baseline compared to 7±4.7 mm after treatment). No substantial changes within the echostructure of the endometrium were observed within the six-month treatment. In the characteristics of the bleeding pattern 64.5% of patients experienced scheduled bleeding, 6.3% of patients had amenorrhea and in 29.2% of patients irregular bleeding episodes were observed. A prolonged bleeding episode was reported by 2.5% of patients. Conclusions: Sequential transdermal oestrogen/progestogen hormone therapy with oestradiol/NETA appears to be effective and safe for endometrium and bleeding pattern and prevents the emergence of hyperplasia.